Faecal carriage of optrA-positive enterococci in asymptomatic healthy humans in Hangzhou, China. (May 2019) - Cai, J.; Schwarz, S.; Chi, D.; Wang, Z.; Zhang, R.; Wang, Y.
Abstract: Objectives: To investigate the faecal carriage of optrA -positive enterococci among asymptomatic healthy humans in Hangzhou, China, and to characterize the genetic context of optrA . Methods: A total of 3458 stool samples from healthy individuals were collected and cultured on a selective medium containing 10 mg/L florfenicol and resulting enterococci were screened for the presence of optrA by PCR. OptrA variants were determined by amino acid sequence comparison with the original OptrA from Enterococcus faecalis E349. Whole genome sequencing and PCR mapping were performed to obtain and analyse the genetic environment of optrA . Results: Similar optrA carriage rates (∼3.5%) were detected in samples from adults (55/1558) and children (66/1900). Linezolid resistance rates for E. faecalis, Enterococcus faecium and other Enterococcus species were 58.5% (38/65), 42.3% (11/26) and 0% (0/31), respectively. Nineteen OptrA variants exhibiting different linezolid MICs were identified. Isolates carrying wild-type OptrA and variants RDK, KLDP, KD, D, RDKP, and EDP generally demonstrated linezolid MICs ≥8 mg/L. The OptrA variants, with fexA upstream and erm(A) downstream, were flanked by IS 1216E at one or both ends. The fexA - optrA (wild-type) was located downstream of a Tn 554 transposon, and was inserted into the radC gene. The EDM variant was detected in 31/73 enterococci with linezolid MICs ≤4 mg/L. Despite the variable genetic context, Tn 558 - araC - optrA (EDM)- erm (A)- met was the most common gene array. Conclusions: This study revealed a correlation between linezolid MIC, genetic context and OptrA variant. Intestinal colonization of healthy individuals by optrA -positive enterococci is a concern, and active epidemiological surveillance of optrA is warranted.